Exploring the Link Between Paranormal Phenomena and Plasma Balls - Galán Santos, Miguel Arsenio; Koren, Stanley (Journal of Scientific Exploration, 2024)
This article explores the relationship between many paranormal phenomena and a proposed type of plasma ball, with two electrically charged layers, referred to in this paper as “Electro-balls”. It provides a framework to explain these weird phenomena as different manifestations of Electro-balls and the mechanisms behind them. These manifestations include unexplained phenomena such as ball lightning, strange sounds in the sky (skyquakes), UFOs/ UAPs, haunted houses, poltergeist phenomenon, levitation, cattle mutilations, cryptids, angels & demons, demonic possessions, etc. It also discusses the electroball formation, its characteristics, and its effects on the environment.